2010
DOI: 10.1111/j.1540-4560.2009.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Bias toward Latinos: Discrimination, Dimensions of Difference, and Experience of Exclusion

Abstract: White-Black relations have historically been the defining form of intergroup relations in the study of prejudice and discrimination. The present article suggests that there are limitations to applying this model to understanding bias toward other groups and proposes that a comprehensive view of the dynamics of the Anglos' bias toward Latinos requires consideration of the distinctive elements of this form of intergroup relations. In four empirical studies, we experimentally document discrimination against Latin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 40 publications
1
115
1
1
Order By: Relevance
“…Like ethnocentric immigration legislation, these policies reproduce White cultural privilege via an assimilation model that requires cultural others to conform to Anglocentric and Eurocentric standards (see Dovidio et al, 2010;Zarate & Shaw, 2010;Zarate & Quezada, 2011). The present research resonates with work on the construction of Whiteness and "possessive investment in Whiteness" (Lipsitz, 2006) and illuminates how public policy can reproduce systems of power that protect the privileges of Anglo-or Eurocentric groups.…”
Section: Theoretical Implications: Varieties Of Threatsupporting
confidence: 66%
“…Like ethnocentric immigration legislation, these policies reproduce White cultural privilege via an assimilation model that requires cultural others to conform to Anglocentric and Eurocentric standards (see Dovidio et al, 2010;Zarate & Shaw, 2010;Zarate & Quezada, 2011). The present research resonates with work on the construction of Whiteness and "possessive investment in Whiteness" (Lipsitz, 2006) and illuminates how public policy can reproduce systems of power that protect the privileges of Anglo-or Eurocentric groups.…”
Section: Theoretical Implications: Varieties Of Threatsupporting
confidence: 66%
“…Furthermore, although the present research focuses on attitudes and behavioral intentions toward Hispanic Americans in particular, future work should examine whether sitnilar results are obtained for other ethnic minority groups in the U.S. Because Hispanic Americans and Asian Americans are often consciously perceived as less American than White or Black Americans (e.g., Cheryan & Monin, 2005;Devos & Banaji, 2005;Dovidio et al, 2010;Yogeeswaran & Dasgupta, 2010;Yogeeswaran et al, 2012), an interesting question is raised; Would the same pattem of results be observed if Asian Americans were used as the target group of interest, but would a different pattem of results be obtained if Black Americans were the target? Future work should explore this question.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…Other research indicates that Whites' attitudes toward Latinos are principally influenced by assumptions regarding language and culture (Dovidio et al, 2010). If so, then the positive bias to Latinos may reflect White teachers' downward shift of evaluative standards (as per Biemat, 2009) to more modest expectations of Latino students' English mastery.…”
Section: Positive Feedback To Latino Studentsmentioning
confidence: 98%